PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA KEKERASAN SEKSUAL PADA ANAK - Siregar, Fitria Ramadhani (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
Based on data obtained from the Gender and Children Information System for North Sumatra Province, in 2022 the number of victims of sexual violence in the city of Medan will be 70 people. These figures show that crimes of sexual violence against children have increased compared to the previous year. According to information from the Head of the PPA Satreskrim Polrestabes Medan Unit, there were 55 reports of perpetrators of sexual violence against children in the jurisdiction of the Medan Police at the end of July 2022, of which 21 people had been detained and the rest had been sentenced at the Medan District Court. Sexual violence against children is a serious crime and a violation of human rights. As an effort to anticipate an increase in sexual violence against children, the government issued a law which was ratified on May 9, 2022 by the Ministry of Law and Human Rights, namely Law Number 12 of 2022 on the Crime of Sexual Violence. It is hoped that the birth of the Law on Crime of Sexual Violence can be optimal in accommodating all forms of violence and can provide protection, prevention, justice and recovery for victims of Crime of Sexual Violence against children.